Low Dimensional Physics and Gauge Principles 2013
DOI: 10.1142/9789814440349_0006
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breaking of Lorentz-Invariance and Gravitons as Goldstone Particles

Abstract: We consider some aspects of spontaneous breaking of Lorentz Invariance in field theories, discussing the possibility that the certain tensor operators may condensate in the ground state in which case the tensor Goldstone particles would appear. We analyze their dynamics and discuss to which extent such a theory could imitate the gravity. We are also interested if the universality of coupling of such 'gravitons' with other particles can be achieved in the infrared limit. Then we address the more complicated mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the aftermath, further physicists took this idea over to gravity to interpret the graviton as a Goldstone boson linked to a spontaneous breakdown of local Lorentz and diffeomorphism invariance [51,52]. More recent works in the context of electrodynamics are [53,54] and for gravity we refer to [55][56][57][58] where the mechanism suggested in [55] is even considered as a solution of the cosmologicalconstant problem. In the context of gravity, it was demonstrated that an alternative gravity theory called cardinal gravity [57,58] can be constructed by means of a bootstrap method from a linearized theory with a two-tensor field that undergoes spontaneous Lorentz violation.…”
Section: The Sme Gravity Sectormentioning
confidence: 99%
“…In the aftermath, further physicists took this idea over to gravity to interpret the graviton as a Goldstone boson linked to a spontaneous breakdown of local Lorentz and diffeomorphism invariance [51,52]. More recent works in the context of electrodynamics are [53,54] and for gravity we refer to [55][56][57][58] where the mechanism suggested in [55] is even considered as a solution of the cosmologicalconstant problem. In the context of gravity, it was demonstrated that an alternative gravity theory called cardinal gravity [57,58] can be constructed by means of a bootstrap method from a linearized theory with a two-tensor field that undergoes spontaneous Lorentz violation.…”
Section: The Sme Gravity Sectormentioning
confidence: 99%
“…This picture has been variously extended to the case of gravity [44,50,51,72,73,146,148,168,183]. For this more exotic case involving tensor fields, the background configuration is identified via conditions of the form…”
Section: Gauge Invariance From Spontaneous Lorentz Violationmentioning
confidence: 99%
“…Spontaneous breaking of spacetime symmetry has been widely investigated both theoretically and experimentally [17][18][19][20][21][22][23][24][25]102,103]. Specific mechanisms for how spontaneous breaking can occur have been identified and explored [14][15][16], and examples and properties of the NG modes that can arise have been studied [29,30,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. In the SME, both the pure-gravity and matter-gravity sectors have been constructed in EC theory [20].…”
Section: Spontaneous Breakingmentioning
confidence: 99%